2015
DOI: 10.1161/circimaging.115.003843
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Atherosclerotic Calcification in Major Vessel Beds on the Risk of All-Cause and Cause-Specific Mortality

Abstract: Background— Atherosclerosis is a major contributor to global morbidity and mortality. Although atherosclerosis is a systemic disease, its burden varies considerably across vessel beds, which may translate into differences in mortality risk. Methods and Results— From 2003 to 2006, a sample of 2408 elderly participants (mean age, 69.6±6.7 years; 52.4% female) from the population-based Rotterdam Study underwent computed tomography to quantify atherosclerot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(66 citation statements)
references
References 44 publications
(46 reference statements)
2
62
0
Order By: Relevance
“…(16) Nonetheless, we found an equally strong association between the ascending and descending aortic atheroma and risk of mortality.…”
Section: Commentmentioning
confidence: 61%
See 1 more Smart Citation
“…(16) Nonetheless, we found an equally strong association between the ascending and descending aortic atheroma and risk of mortality.…”
Section: Commentmentioning
confidence: 61%
“…(15) Atherosclerotic load in major vessel beds is associated with an increased risk of death. (16) When comparing atheromatous disease in the coronary arteries, aortic arch, extracranial carotid arteries, and intracranial carotid, Bos. et al found that aortic arch atherosclerosis was found to be associated with the greatest increase in mortality.…”
Section: Commentmentioning
confidence: 99%
“…Prior studies have demonstrated the important role of calcification in the aortic arch and descending thoracic aorta. 3,23 Furthermore, many associations that were observed were of borderline or no statistical significance, possibly due to the small sample size of participants with ATAC and insufficient statistical power. Second, in the Agatston method, density scores are arbitrarily capped at a maximum value of 4, potentially underestimating the inverse association of ATAC density with CHD and CVD in plaques of attenuation in excess of 400 HU.…”
Section: Discussionmentioning
confidence: 98%
“…Evidence for the harms of nontraditional risk factor assessment was limited to 8 studies evaluating CAC score; no eligible studies evaluated the potential harms of the ABI or hsCRP level. Four studies reported radiation exposure for CT imaging to obtain CAC score, 43,55,62,75 and 5 studies reported other potential adverse events from CAC score measurement such as psychological outcomes, adverse cardiovascular events, and health care utilization. 45,66,67,75,80 Overall, the radiation exposure or effective radiation dose per CT examination is low: 2 mSv or less.…”
Section: Harms Of Risk Assessmentmentioning
confidence: 99%